2020
DOI: 10.2478/adms-2020-0022
|View full text |Cite
|
Sign up to set email alerts
|

EBSD Characterization of Bobbin Friction Stir Welding of AA6082-T6 Aluminium Alloy

Abstract: Electron Backscatter Diffraction (EBSD) was used to determine microstructural evolution in AA6082-T6 welds processed by the Bobbin Friction Stir Welding (BFSW). This revealed details of grain-boundaries in different regions of the weld microstructure. Different polycrystalline transformations were observed through the weld texture. The Stirring Zone (SZ) underwent severe grain fragmentation and a uniform Dynamic Recrystallisation (DRX). The transition region experienced stored strain which changed the grain si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…The EBSD results confirmed that for the Al alloys with the FCC structure [37] the precipitation occurred at two positions: the HAGBs between the main grains and also within the grain at the LAGBs. The increased density of the participate particles deposited at the LAGBs contributes to strain hardening as the blocking barriers of dislocation movement.…”
Section: Microstructure Evolutionsupporting
confidence: 71%
See 2 more Smart Citations
“…The EBSD results confirmed that for the Al alloys with the FCC structure [37] the precipitation occurred at two positions: the HAGBs between the main grains and also within the grain at the LAGBs. The increased density of the participate particles deposited at the LAGBs contributes to strain hardening as the blocking barriers of dislocation movement.…”
Section: Microstructure Evolutionsupporting
confidence: 71%
“…The comparison between the microstructures shows that the grain morphology has a similar trend in the coarseness of the morphological features with the increase of the welding speeds. Although the dynamic recrystallized structure was formed for all the samples, the differences in apparent coarseness of the grain size indicate more severe plastic deformation has been increased by elevating the welding speeds [27,37]. Figure 9c and Figure 10c demonstrate a morphological comparison of the AA1100 and AA3003 samples in the maximum speeds (600 rpm and 400 mm/min), respectively.…”
Section: Microstructure Evolutionmentioning
confidence: 98%
See 1 more Smart Citation
“…Consequently, by the simultaneous pin action localized at the mid-SZ, the dissimilar joining bond layer forms at the interface of the Aluminium and Copper. It should be noted that the interruption in the refilling process disintegrates the deposition of the plastic layers transferred to the backing edge of the tool [31]. Therefore, the failure of the intermixing causes the flow discontinuity in the form of the void defect.…”
Section: Materials Flow-phenomena In Metallic Jointsmentioning
confidence: 99%
“…These IMCs deteriorate the mechanical properties [5] and lead to the rapid fracture of the joints [7]. Recently, new studies on friction stir welding (FSW) have been widely increasing with the focus on the joining of dissimilar metals [3,8], whereas pair metals in automotive and manufacturing industries are highly demanded. The FSW offers numerous advantages such as enhanced fatigue resistance, tensile properties, process quality, and reduced IMC formation, in addition to lower operating costs, energy efficiency, and being environmental and health friendly [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%